MONOPOLISTIC PORT BUSINESS ACTIVITIES POST-DEMONOPOLIZATION OF PT.PELINDO (PERSERO) BASE ON BUSINESS COMPETITION LAW - Putu Samawati Saleh (Kanun Jurnal Ilmu Hukum, 2022)
Since the implementation demonopolization of port business activities in 2008, the condition of Indonesian port business competition still dominates of PT.Pelindo (Persero) with market share od 84%. Even though the state has imposed a demonopolization policy with the aim of opening up opportunities for private port business entities to become competitors for PT.Pelindo (Persero). The monopolistic condition of PT Pelindo (Persero) is the reason to discuss in this paper. Finding mind problem in normative construction to get some solution are also be a purpose of this article. A normative juridical research and a statutory approach was carried out to find legally what was wrong in the port management mechanism. The expected results are in the form of normative improvement efforts that can be made in an effort to increase competition in port services, particularly in regards to restoring the role of port authorities and affirming the regulation of the separation of roles between port authorities and port business entities. This improvement is necessary, given the important role of ports as connectivity and mobility in Indonesia.